Existe-t-il une réception homosexuelle ? - Alain Brassart (Mise au Point)
The object of this article is to question the existence of the sort of "cobbled together" reading (a term dear to Michel de Certeau) that homosexual audiences undertake. For the most part in film analysis the role of how a film is received is not taken into account as the audience is usually seen as the "ideal receiver". However, the German literary critic Hans-Robert Jauss thinks that the meaning of a work is found in the "dialogue" between the text itself and the reader. Thus, the work ceases to be considered, like in structuralism, as a closed system, independent of its production. While the comments by film buffs (particularly in France) tend to demonstrate a certain coherence in the discourse as well as in the artistic project, it is undeniable that each film is "read," or interpreted differently by the audience according to their "race," their age, their sexual identity or their sexual orientation . Trying to show that there is a homosexual reception is not an easy task. Indeed the gay press is a minority one and the film critics that it proposes are often brief or concise, which makes a textual analysis necessary.